Active Workstations to Fight Sedentary Behaviour. - Torbeyns, Tine; Bailey, Stephen; Bos, Inge; Meeusen, Romain (Sports Medicine, 2014)
Background: The impact of active workstations has been studied in several settings, and several outcomes have been investigated. However, the effects on health, work performance, quality of life, etc., have never been systematically reviewed. Objective: To evaluate the existing literature about active workstations and their possible positive health and work performance effects. Data Sources: We searched the electronic databases PubMed and Web of Science (up until 28 February 2014). The search terms we used were 'active workstation', 'standing workstation', 'standing desk', 'stand up workstation', 'stand up desk', 'walking desk', 'walking workstation', 'treadmill workstation', 'treadmill desk', 'cycling workstation', 'cycling desk' and 'bike desk', in combination with 'health', 'quality of life', 'cognition', 'computer task performance', 'absenteeism', 'productivity', 'academic achievement', 'cognitive decline', and 'independent living'. In addition, we searched the reference lists of relevant published articles. Study Selection: Randomized controlled trials, non-randomized controlled trials and non-randomized non-controlled trials investigating the introduction of active workstations in humans were included in this systematic review. Only original studies were included, and we did not accept studies combining the introduction of active workstations with other interventions. Outcomes concerning health, energy expenditure, cognition, quality of life and work performance were included. Results: We included 32 studies, of which five were longitudinal studies in school-aged children, 10 were longitudinal studies in adults and 17 were non-longitudinal studies in adults. Sixteen studies investigated standing desks, 15 investigated walking desks, and one investigated a cycling workstation. The general findings were decreased sitting time, increased energy expenditure, a positive effect on several health markers, no detrimental effect on work performance, no acute effect on cognitive function and no straightforward findings concerning computer task performance. Conclusion: The implementation of active workstations might contribute to improving people's health and physical activity levels. The effect of the use of these active workstations on cognition and applied work tasks, such as computer task performance, needs further investigation before conclusions can be drawn. Another aspect that needs further investigation is the implementation of the different active workstations in all age groups.